Further characterization of ATP6V0A2-related autosomal recessive cutis laxa - Fischer, Bjoern; Dimopoulou, Aikaterini; Egerer, Johannes; Gardeitchik, Thatjana; Kidd, Alexa; Jost, Dominik; Kayserili, Hulya; Alanay, Yasemin; Tantcheva-Poor, Iliana; Mangold, Elisabeth; Daumer-Haas, Cornelia; Phadke, Shubha; et al. (SPRINGER, 2012)
Autosomal recessive cutis laxa (ARCL) syndromes are phenotypically overlapping, but genetically heterogeneous disorders. Mutations in the ATP6V0A2 gene were found to underlie both, autosomal recessive cutis laxa type 2 (ARCL2), Debr, type, and wrinkly skin syndrome (WSS). The ATP6V0A2 gene encodes the a2 subunit of the V-type H+-ATPase, playing a role in proton translocation, and possibly also in membrane fusion. Here, we describe a highly variable phenotype in 13 patients with ARCL2, including the oldest affected individual described so far, who showed strikingly progressive dysmorphic features and heterotopic calcifications. In these individuals we identified 17 ATP6V0A2 mutations, 14 of which are novel. Furthermore, we demonstrate a localization of ATP6V0A2 at the Golgi-apparatus and a loss of the mutated ATP6V0A2 protein in patients' dermal fibroblasts. Investigation of brefeldin A-induced Golgi collapse in dermal fibroblasts as well as in HeLa cells deficient for ATP6V0A2 revealed a delay, which was absent in cells deficient for the ARCL-associated proteins GORAB or PYCR1. Furthermore, fibroblasts from patients with ATP6V0A2 mutations displayed elevated TGF-beta signalling and increased TGF-beta 1 levels in the supernatant. Our current findings expand the genetic and phenotypic spectrum and suggest that, besides the known glycosylation defect, alterations in trafficking and signalling processes are potential key events in the pathogenesis of ATP6V0A2-related ARCL.